PENGEMBANGAN MODUL AJAR BERBASIS BUDAYA BETETULAK SERIBU DULANG UNTUK MENINGKATKAN KARAKTER ANAK KELOMPOK B TK NEGERI 2 PRINGGASELA - Rismayanti, Susi; Nurhasanah; Nada Buahana, Baiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a teaching module based on the Betetulak Seribu Dulang culture to improve the character of Group B children at TK Negeri 2 Pringgasela and to determine the feasibility and effectiveness of the developed teaching module. This research employed the Research and Development (R&D) method using the 4D development model, which consists of the define, design, develop, and disseminate stages. The research subjects were 30 Group B children at TK Negeri 2 Pringgasela. Data were collected through observation, interviews, questionnaires, and documentation. The feasibility data of the teaching module were analyzed using quantitative descriptive analysis based on the validation results of material experts, media experts, and teacher practitioners’ responses, while the effectiveness of the module was analyzed using the N-Gain test. The results showed that the module was categorized as highly feasible with material expert validation of 96.4%, media expert validation of 92.8%, and teacher practitioner responses of 96.7% and 93.3%. The effectiveness was indicated by an N-Gain score of 0.4683 or 46.83%, which falls into the moderate category. These results indicate that the module is effective in improving children’s character through contextual, enjoyable, and local culture-based learning activities. Keywords: Betetulak Seribu Dulang, Early Childhood Character, Teaching Module Development.